Exploitation of private agricultural property in Algerian law - Hatem, Mouloud (Revue jurisprudence; Vol. 11 No 02 (2019): مجلة الاجتهاد القضائي, 2019)
Agricultural real estate, whether public or private, is a basic rule in economic life, so it has received considerable legal attention in order to maintain and promote it through its effective exploitation, as evidenced by the promulgation of a series of real estate legislation, the most important of which is Law No. 90-25, which contains The real estate directive, which re-considered the real estate property of its repeal of the Agricultural Revolution Act.